ANALISIS PERDAGANGAN BERAS DAN KETAHANAN PANGAN DI NEGARA-NEGARA ASIA TENGGARA - Iwan Hermawan (Jurnal Politica, 2013)
Rice trade has function to maintan sufficient rice stock for fulfill domestic demand. Some of main rice exporter and importer countries in world market are in Southeast Asia region, so changing in traded rice quantities will influence trade flow. Rice as strategies commodities and so many countries have intervented in domestic rice market to achieve food security and political security. The aim of this paper is analysis of development of rice trade in southeast asia countries related with food security. Anlysis desciptive approached is applied to answer that aim. The result showed that in 2005-2012, growth rate of rice impor in Southeast Asia countries is 14,08 percent and dan rice consumption share is more than 22 percent to world rice consumption. Growth rate of its rice export is 2,21 percent and supporting paddy production share is more than 30 percent to paddy production in the world. Government has intervented rice market through international trade, such as rice export ban and license scheme, and domestic rice price stabilization policy to maintan rice stock refer to food security. Economic integration through ASEAN Economy Comunnity will be a important moment as a base to achieve food security and making rice market more opened intra-Southeast Asia countries.